Proposta de material didático bilíngue Português-Mbya: um estudo sobre classificação (léxico-semântica) e formação de palavras no Guarani Mbya - Silva, Algemiro da (2024)
Presents a proposal for bilingual – Portuguese-Mbya – didactic material for the teaching-learning process of Mbya language (Guarani Mbya). The teaching material is titled “Ayvu mba’emo porã a’e ayvu mba’emo vai: como se classificam e se formam as palavras no Guarani Mbya?” (Ayvu mba’emo porã a’e ayvu mba’emo vai:how words are formed and classified in Guarani Mbya?) and was produced from a didactic approach to lexical aspects of the Mbya language; it involves i) a lexical-semantic classification (two classes, the words for “good things” and the words for “bad things”), ii) the processes for word formation (derivation, composition, inflection), and iii) the phenomena of obsolescence, neologism, and borrowing, that highlight the relationship between the study of the language (grammar) and the Mbya knowledge (cosmogony). Directed to elementary school indigenous teachers of Mbya schools, the material aims at provoking the teachers into metalinguistic reflections on their mother tongue, and, at the same time, provides teaching support for the Mbya language classes. This bilingual approach (Portuguese-Mbya) reflect the political, educational and linguistic decisions made by the representatives of the Colegio Indígena Estadual Karai Kuery Renda (State Indigenous School Karai Kuery Renda - CIEKKR), of the Aldeia Sapukai (Sapukai indigenous village), from Angra dos Reis, RJ, and of the Curso de Ensino Médio com Habilitação em Magistério Indígena Guarani (High School with habilitation in Indigenous Guarani Teaching), in the State of Rio de Janeiro, who favored a bilingual, intercultural and differentiated education.